Sharing health-related stigma through selfies and its perceived potential for de-stigmatization - Allen, Marie Sherrill, author; Martey, Rosa Mikeal, advisor; Dunn, Thomas, committee member; Long, Marilee, committee member (Colorado State University. Libraries, 2018)
This study explores the impact of posting selfies on perceptions of stigma surrounding health conditions. Using Goffman's stigma theory, it examines the communicative role of posting selfies that explicitly portray signs and symptoms of health conditions. The study uses eight one-on-one interviews with creators of what this thesis calls stigma signaling selfies (SSS) posted on the social media platform Instagram. It focused on people with cancer who posted SSS in order to understand motivations for and perceived consequences of posting. Interviews revealed that posting SSS provided a low-pressure way to disclose their cancer diagnoses and treatments, helped creators build closer relationships with others who have cancer, and promoted conversation about and normalization of cancer in public communication on the social media platform. In these ways, selfies fulfill each role of what stigma theory proposes revealing stigma plays for stigmatized individuals: disclosure, identity construction, and de-stigmatization. As one of the first formal research projects to study SSS, this study aims to create a starting point for future work at the intersection of selfies and stigma.